A study of a rural community -- its provisions for health, education and welfare - Felizmena, Remedios C. 1922- ([Quezon City University of the Philippines], 1952)
This study supplies the citizenry with background information, from which they can solve the problem of supplying what the community lacks and improve what the community has to offer. The study seeks to portray a rural community-- its setting, the founding and development of the community, the system of local government, the chief economic and industrial factors which condition the life of its people, the educational resources, religious agencies, welfare and health provisions and attitudes, and beliefs and superstitions of the people.
Bibliography: p. 187-189.
Thesis (M.Ed.)--University of the Philippines, 1952
Typewritten
Vita
Keywords: Sta. Catalina, Ilocos Sur -- Social life and customs; Community life